The OECD model convention, 1998 and beyond : the concept of beneficial ownership in tax treaties : proceedings of a seminar held in London in 1998 during the 52nd Congress of the International Fiscal Association /: the concept of beneficial ownership in tax treaties : proceedings of a seminar held in London in 1998 during the 52nd Congress of the International Fiscal Association. (2016) - Unknown
No abstract available